THE EXPERIENCE OF MAPPING LINEAMENTS AND RING STRUCTURES USING GIS: (on the example of Eastern Vayk) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article describes the experience of using the geographical information system (GIS) for recognizing lineaments and ring structures that are weakly developed on the surface. The selection of the latter is crucial for the reasonable selection of ore taxon of different orders – ore knots, fields and deposits, which contributes to the efficiency of geological exploration work. The results of the research allowed us to present the structural features of the studied territory in a new way.
Keywords: lineaments; ring structures; geomorphology; GIS; digital elevation models; raster images of shaded relief